Elevation Matrix Data in the Evaluation of Keratoconus and Normal Corneas - Tejedor, Jaime; Gutierrez Carmona, Francisco José (My University, 2022)
Introduction: To determine whether elevation matrix data of the anterior corneal surface could be useful for the diagnosis of keratoconus. Methods: In a cross-sectional study, subjects aged 10¿40 years with keratoconus (n = 74) or age-matched controls (n = 36) underwent complete ophthalmological examination, including Scheimpflug corneal topography (Pentacam HR). Exclusion criteria comprised previous ocular surgery, other eye disease, or significant corneal scarring. A raw data matrix of distance measurements to the most anterior corneal point was used to compare each subject with the mean normal cornea. A central 6-mm zone (6.1 9 6.1 mm) and two inferior eccentric matrices (0.4 9 6.1 and 1.1 9 1.1 mm) were used. Outcome measures were sensitivity, specificity, positive and negative predictive value, likelihood ratio, accuracy, and odds ratio. Results: Sensitivity of central matrix for the diagnosis of keratoconus was low (6.7%) whereas specificity reached 94.4%. Sensitivity and specificity were respectively 93.2% and 94% for the 6.1 9 0.4 mm eccentric matrix and 97.2% and 97.2% for the 1.1 9 1.1 mm eccentric matrix. Positive predictive and negative predictive values were 71.4% and 33%, respectively, for the central matrix; 97.1% and 87.1%; 98.6% and 94.5%, for the two eccentric matrices, respectively. The likelihood ratio of a positive test was 1.1, 16.7, and 35, respectively. Sensitivity and specificity of the eccentric matrices were significantly better in the diagnosis of subclinical keratoconus (but not definite keratoconus) than other Pentacam indices. Conclusions: Using eccentric elevation matrix data analysis of the cornea is useful in the detection of keratoconus versus normal corneas. Keywords: Cornea; Elevation data; Keratoconus; Refractive surgery